Parenteral micronutrient supplementation enhances mammary immune function and colostrum–milk quality by modulating cytokine profiles and oxidative stress in transition crossbred cows - Somagond, Yallappa M.; Das, Pravasini; Dang, Ajay Kumar; Yadav, Dhawal K.; Kittur, Priyanka M.; Panda, Bibhudatta S.K.; Devi, Pooja; Kamboj, Aarti; Alhussien, Mohanned Naif (Frontiers in Immunology, 2025)
BackgroundThe transition period in dairy cattle is marked by oxidative stress and immune suppression linked to altered micromineral status. This study evaluated whether parenteral supplementation with trace elements and vitamins could enhance mammary health and improve the immunonutritional quality of colostrum and milk.MethodsTwenty-four multiparous cross-bred cows were blocked by parity and projected yield, then assigned to control, multivitamin (MV; vitamins A, B-complex, D₃, E), multi-mineral (MM; Copper (Cu), Manganese (Mn), Selenium (Se), and Zinc (Zn)), or combined multivitamin and multi-mineral (MMMV) groups. Intramuscular injections were administered on days −30, −15, −7, 0, +7, +15, and +30 relative to calving. Longitudinal sampling was conducted on days 0, 2, 3, 4, 7, 15, and 30 postpartum.ResultsMMMV cows produced colostrum and milk with higher fat and protein percentages, stable lactose, and greater concentrations of insulin-like growth factors and immunoglobulins than all other groups (P < 0.05). Mammary health indicators improved concomitantly: somatic cell counts fell, the neutrophil-to-macrophage ratio normalised, and phagocytic activity of both cell types increased. These functional improvements were accompanied by reduced expression of toll-like and chemokine receptors in milk phagocytes. Additionally, the cytokine profile shifted toward an anti-inflammatory state evidenced by lower levels of IL-1β, IL-6, IL-8, IL-17A, and IFN-γ, and higher levels of IL-4 and IL-10. Reduced oxidative stress was indicated by decreased activities of superoxide dismutase, catalase, and glutathione peroxidase in the milk whey of the MMMV group. The MM and MV treatments conferred intermediate benefits, whereas the control group showed the greatest inflammatory and oxidative stress.ConclusionsRepeated parenteral delivery of complementary trace minerals and vitamins throughout the transition period enhances mammary innate immunity, attenuates inflammation and oxidative stress, and augments the nutritive and immunological value of colostrum and milk. This approach offers a practical intervention to safeguard udder health and optimise passive immune transfer to calves.